The Relationship Of Knowledge, Attitude Of Pregnant Women and Access to Health Services With Pregnancy Check Visits At Puskesmas Blangkejeren District Gayo Lues Year 2017 - Hariyati Wahyuni; Junita; Karnirius Harefa (TOUR HEALTH JOURNAL, 2023)
Background: Antenatal Care during pregnancy aims to detect the occurrence of high risk of pregnancy, labor and also reduce maternal mortality and monitor the condition of the fetus. Based on data of ANC in 2016 at Health Center Blangkejeren Gayo Lues Regency K1 = 82% and K4 = 78%, while target of Minimum Service Standard about health according to Minister of Health Decree no. 43 years 2016, K1 = 100% and K4 = 95.9%. This can be prevented by regular pregnancy checks to detect risks. Purpose: The purpose of this study is the relationship of maternal attitude attitudes and access with the visit of pregnancy examination in Puskemas Blangkejeren Gayo Lues District. Method: The type of research used is analytic with cross-sectional design. The population in this study were all 3 trimester pregnant women at Blangkejeren Community Health Center of Gayo Lues Regency obtained in September 2017 as many as 311 people. The sample of this research is 75 people by using accidental sampling technique. The collection of research instruments in the form of questionnaires. Results: Data analysis was tested by chi-square knowledge of pregnant mother of majority good (52%), attitude of majority of positive (66,7%) and access of majority service easy to reach as much (64%). There was a correlation between pregnant women's knowledge with prenatal visit (p = 0,030) p <0,05, there was correlation between attitude of pregnant mother and pregnancy visit (p = 0,008) p <0,05, p = 0,011) p <0,05. The result of analysis using multiple logistic regression is known that most influential to visit of pregnancy examination that is attitude with value p = 0,004 and OR 4,571. Disscusion and Conclusion: For puskesmas it is suggested to improve counseling to pregnant mother about pregnancy test.